Fly model sheds light on brain disease. - Berryer, M.H.; Kosmaczewski, S.G.; Barrett, L.E. (eLife, 2019)
Experiments on flies suggest that a gain-of-function mechanism in a protein called CSP? contributes to the progressive brain disease CLN4.